2015
DOI: 10.1007/s10620-015-3872-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting a Response to Antibiotics in Patients with the Irritable Bowel Syndrome

Abstract: A lactulose breath test appears to be useful in predicting response to antibiotics in patients with the irritable bowel syndrome. A hydrogen + methane rise <20 ppm throughout the duration of the test is most predictive. This observation contradicts the classic definition of a positive lactulose breath test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Moreover, SIBO‐related symptoms were common in IBS such as abdominal discomfort, bloating, and flatulence . Treatment‐presumed SIBO with antibiotics, such as rifaximin, has been shown to improve IBS symptoms in at least 40% of subjects . It further supports the potential roles of SIBO in IBS and may predict a response to antibiotics in these patients …”
Section: Introductionmentioning
confidence: 69%
“…Moreover, SIBO‐related symptoms were common in IBS such as abdominal discomfort, bloating, and flatulence . Treatment‐presumed SIBO with antibiotics, such as rifaximin, has been shown to improve IBS symptoms in at least 40% of subjects . It further supports the potential roles of SIBO in IBS and may predict a response to antibiotics in these patients …”
Section: Introductionmentioning
confidence: 69%
“…Therefore, the above findings should be interpreted with caution. Nevertheless, two recent studies 76,77 have shown that a positive H 2 BT does predict symptomatic response to antibiotic therapy in patients with IBS. A thoughtful Editorial 78 actually suggested that breath testing for SIBO could represent a mean to enrich rifaximin responders amongst IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that antibiotic therapy reduces the effects of methanogenic bacteria, given that patients with IBS, particularly IBS-C, were shown to have increased fecal concentrations of the methanogen Methanobrevibacter smithii compared with healthy individuals; further, methane producers by breath testing had greater concentrations of M. smithii [115]. However, a retrospective study of patients with IBS receiving antibiotic treatment reported that the best therapeutic response occurred in patients who had no increase in measured hydrogen and methane gases in a lactulose breath test [116]. Thus, while some evidence suggests that methanogenic bacteria may play a role in response to antibiotics, further study is needed.…”
Section: Antibioticsmentioning
confidence: 99%